Associations of Serum Urate and Cardiovascular Events in a Clinical Trial of Interleukin-1β Blockade - Nicholas H. Adamstein, MD; Jean G. MacFadyen, BA; Brittany N. Weber, MD, PhD; Peter Libby, MD; Daniel H. Solomon, MD, MPH; Paul M Ridker, MD, MPH (JACC: Advances)
Background: Serum urate (SU) associates with cardiovascular (CV) events, mortality, and gout. Objectives: The purpose of this study was to assess whether SU predicts CV risk in a trial of interleukin (IL)-1β inhibition with canakinumab, and whether IL-1β blockade, kidney function, or gout alter these associations. Methods: This study is a subanalysis of the Canakinumab Antiinflammatory Thrombosis Outcome Study (CANTOS), which randomized 10,061 patients with prior myocardial infarction and elevated high-sensitivity C-reactive protein to 3 doses of canakinumab or placebo. SU was measured at baseline. Cox proportional hazards models compared major adverse cardiovascular events (MACE), CV death, and all-cause mortality among those with SU ≤6.8 mg/dL (normal), 6.8 to 9.0 mg/dL (elevated), and ≥9.0 mg/dL (markedly elevated). Cox regressions were repeated within subgroups, including canakinumab vs placebo, estimated glomerular filtration rate ≥60 vs <60 mL/min, and gout vs no gout. Results: Markedly elevated SU associated with MACE (HR: 1.66 [95% CI: 1.38-1.99]; P < 0.0001), CV death (HR: 2.52 [95% CI: 1.98-3.21]; P < 0.0001), and all-cause mortality (HR: 2.43 [95% CI: 2.01-2.94]; P < 0.0001) compared to normal SU. After multivariable adjustment for a minimal set of potential confounders, SU independently predicted all 3 endpoints. Associations were unchanged after IL-1β blockade with canakinumab. For normal estimated glomerular filtration rate, SU associated with CV and all-cause mortality, but not MACE. Participants with gout had higher event rates independent of SU. Conclusions: In over 10,000 patients with coronary artery disease, individuals with markedly elevated SU have elevated CV risk despite aggressive treatment. IL-1β blockade did not modify these associations. Baseline kidney function and monosodium urate deposition may function as effect modifiers.